Efficacy of Early Therapeutic Hypothermia after Cardiac Arrest on Neurological Outcome in ICU Patients - Muhammad Sohaib, Syed Mazhar Ali Naqvi, Muhammad Haseeb Ishaq, Muhammad Usman Jahangir, Akhtar Ali, Imran Sharif Ansari, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective:To learn about efficacy of early therapeutic hypothermia affects neurological outcomes in post cardiac arrest patients. Study design: Quasi Experimental study. Place and duration of study: Study was conducted from May 2021 to Feb 2022 at Department of critical care management services hospital Lahore. Methodology: Patients having age 18 to 70 years were included in the study. The daily neurological assessment was carried out when sedation was off till patient was discharged by critical care physician. The results were expressed in cerebral performance categories On the basis of neurological outcome patients were divided in two groups. Group A (good outcome) consists of patients of cerebral performance category 1 and 2, while group B (poor outcome) consists of patients of cerebral performance category 3 and 4. Results: Total 60patients were included in study. 10 patients of group A and 22 patients of group B have died during hospital stay. Mean age of patients in Group A (good prognosis) was 56.72 ± 9.11 years and in Group B (poor prognosis) it was 53.85 +7.95 years. The starting temp which was taken before inducing hypothermia was 35.28 0C (mean) in group A and 35.75 0C in group B which was statistically significant (p= 0.04). Coldest temp achieved in group A was 33.07 0C and in group B it was 33.25 0C which was statistically significant (p= 0.01). Conclusion: Among patients of in hospital cardiac arrest the overall survival rate and better neurological outcome was seen in patients in whom therapeutic hypothermia was induced as soon as possible after successful resuscitation as compare to those in which usual treatment was given. Keywords: cardiac arrest, therapeutic hypothermia